Testosterone, androstenedione, cortisol, triiodothyronine and thyroxine hormonal profile in neonate male buffaloes - Ohashi, O. M.; Oba, Eunice [UNESP]; Nogueira, JR (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1997)
Basic aspects of the hormonal profile of five hormones were studied in neonate male buffaloes. The level of testosterone (T), androstenedione (A), cortisol (C), triiodothyronine (T3) and thyroxine (T4) were determined during the period of 1-6, 7-8, - 9-12, 24, 48, 72 and 96 hours after parturition, using RIA solid phase technique. All hormones studied presented high levels in the neonate animals. The T and A levels were high in the first 1-6 hours post-partum, being 99.6+/-66.6 and 1,301.4+/-887.7 pg/ml, respectively. The T decreased sharply to basal levels (below the analysis limit of detection) within 24 hours while the A reached the basal level within 48 hours with 348.0+/-279.4pg/ml. The C and T4 levels were also high in the first 24-48 hours, which levels were 5.0+/-3.2 and 11.1+/-2.6 mu g/ml, respectively, decreasing gradually and significantly (P<0.01) until 96 hours post-partum, when they approached the basal levels (1.2+/-1.5 and 7.2+/-2.7 mu g/ml, respectively). The concentration of T3 remained elevated during the entire period of sample collection with little variation (P>0.05), with levels of 328.6+/-130.8 and 294.5+/-134.9ng/dl, respectively during 1-6 hours and 96 hours after parturition.
Keywords: buffalo; hormonal profile